Challenges of Online Boarding Schools In The Digital Era - Kardi Kardi; Hasan Basri; Andewi Suhartini; Fitri Meliani (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2023)
The virtual world has caused disruption in various social lives and institutions, including Islamic boarding schools. This oldest religious institution in Indonesia has also redefined its meaning, thus building a new stream called